ENVIRONMENT CONTENT IN THE CULTURE PUBLIC HIGH SCHOOL IN CIMAHI AS EFFORTS TO GROW THE STUDENTS ECOLOGICAL INTELLIGENCE - Mainaki, Revi (Jurnal Pendidikan Geografi Gea, 2017)
The environmental damage becomes a problem that must be considered globally, especially in Indonesia. Cimahi as one of the cities in Indonesia, supporting the activities of West Java Province because of its strategic location, the preservation of the environment needs to be maintained. The high impact of the environmental damage is seen from the people with diseases due to environmental degradation as well as industrial growth and lack of green open space, make it must be vigilant. Through survey method with qualitative approach, descriptive data analysis techniques, data collected through interviews, documentation studies, and literature study, this research aims to measure the environmental content in secondary school culture at Cimahi, because it can, at least, develop students’ ecological intelligence who are at age range 12-18 years where intelligence is very vulnerable to form. As for the environmental content classification in school culture is classified into low (1,000-2,093), moderate (2,094-3,186), and high (3,187-4, 28). Based on the results of the research, most of the secondary schools are in the moderate and high classification, the highest aspect is exemplary of principles, teachers, and educators in providing examples of school environment preservation, while the lowest aspect is in the school physical environment and environment preservation based participatory activities.